2009
DOI: 10.1179/136485909x435120
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology of sporadic acute hepatitis in Bangladesh: high prevalences of infection with type-B, type-E and multiple types of hepatitis virus

Abstract: In a recent investigation of hepatitis in Bangladesh, the sera from 74 adult patients (aged 15-67 years) who had been clinically diagnosed as cases of sporadic acute hepatitis were collected at various hospitals in and around Dhaka. Five cases were positive for IgM antibody against the hepatitis A virus and 30 were positive both for the surface antigen of the hepatitis B virus (HBV) and for IgM antibody against the HBV core (HBc). The six cases found positive for antibodies against the hepatitis D virus were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…86,87 HEV is also recognized as the causative agent in most cases of acute, sporadic hepatitis. 33,88 A recent population-based study of maternal mortality from Bangladesh suggested that nearly 10% of maternal (pregnancy-related) mortality is likely associated with HEV infection. 89…”
Section: South Asiamentioning
confidence: 99%
“…86,87 HEV is also recognized as the causative agent in most cases of acute, sporadic hepatitis. 33,88 A recent population-based study of maternal mortality from Bangladesh suggested that nearly 10% of maternal (pregnancy-related) mortality is likely associated with HEV infection. 89…”
Section: South Asiamentioning
confidence: 99%
“…38% has been reported in previous studies in China (34)(35)(36)(37)(38). In Southeast Asia, the HBV-HEV superinfection rate was reported to be 45%, 14% and 9.5% in Vietnam, India and Bangladesh, respectively (39)(40)(41). A clear territory-wise distribution of HBV-HEV superinfection has been observed in Africa where a higher prevalence of 56.7% was reported in Egypt in the northern part of the continent, while insignificant rates of 1% and 0% were reported in Kenya, the Eastern part of Africa (27,42,43) (Table 1).…”
Section: Epidemiologymentioning
confidence: 80%
“…Even more alarming is the fact that HBV seems to be major etiological agent of both acute and fulminant hepatitis in Bangladesh. Sugitani et al have reported that HBV was the main etiological factor of sporadic acute hepatitis, and 36% adult patients with sporadic acute hepatitis B in their cohort were infected with the HBV 15 . Another study conducted by us also revealed that about onethird patients with fulminant hepatic failure were infected with the HBV in Bangladesh 16 .…”
Section: Resultsmentioning
confidence: 99%